Achieving high-energy-density and ultra-stable zinc-ion hybrid supercapacitors by engineering hierarchical porous carbon architecture - Yu, Peifeng; Zeng, Yuan; Zeng, Yinxiang; Dong, Hanwu; Hu, Hang; Liu, Yingliang; Zheng, Mingtao; Xiao, Yong; Lu, Xihong; Liang, Yeru (Electrochimica acta, 2019)
Zinc-ion hybrid supercapacitor emerges as a promising energy storage device in benefit of the merits from both battery and supercapacitor. However, the challenges induced by the low energy density and poor cycling stability of the cathodes hinder the practical applications of zinc-ion hybrid supercapacitors. To address these issues, a structural engineering of carbonaceous cathode into a hierarchical porous architecture based on a hydrothermal-assisted molecular-scale mixing strategy is proposed. The key structures of the as-fabricated hierarchical porous carbon consist of high specific surface area, well-interconnected hierarchical porous morphology and favorable graphitization degree with good conductivity, which promises great conceptual and technological potential for high-performance zinc-ion storage. It is demonstrated that the high specific surface area supply sufficient active sites for zinc-ion storage, and collectively, the valuable hierarchical porous structure and high electric conductivity are beneficial for rapid transfer/diffusion of zinc ion. An ultrahigh capacity of 305 mAh g−1, a high energy density of 118 Wh kg−1, good rate capability, and excellent cycling stability of over 94.9% after 20000 cycles at a high current density of 2 A g−1 can be achieved when hierarchical porous carbon is used as the cathode of a zinc-ion hybrid supercapacitor. [Display omitted] •High-energy-density and ultra-stable zinc-ion hybrid supercapacitors are realized.•Hierarchical porous carbon is obtained based on a purposeful hydrothermal-assisted molecular-scale mixing strategy.•High surface area, hierarchical porous architecture and favorable graphitization degree is favorable to zinc-ion storage.